2021
DOI: 10.1109/access.2021.3074713
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automatic Model Based on SE-ResNet for Bone Age Assessment

Abstract: Bone age assessment (BAA) based on hand X-ray imaging is a common clinical practice for investigating disorders and predicting the adult height of a child. However, the traditional manual method is time consuming and prone to obverse variability. There is an urgent need for a fully automatic framework based on deep learning with high performance and efficiency. We propose an end-to-end BAA model based on lossless image compression and a squeeze-and-excitation deep residual network (SE-ResNet). First, we apply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 25 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…Taking out the inception layer essentially created a ResNet based model with SE blocks added. Several studies have reported that adding SE blocks to the base ResNet increased performance (Xu and Zhang, 2020 ; He and Jiang, 2021 ). When tested on the ImageNet validation set, there was also a decrease in error by 0.86% which is in agreement with our results (Rodrigues et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking out the inception layer essentially created a ResNet based model with SE blocks added. Several studies have reported that adding SE blocks to the base ResNet increased performance (Xu and Zhang, 2020 ; He and Jiang, 2021 ). When tested on the ImageNet validation set, there was also a decrease in error by 0.86% which is in agreement with our results (Rodrigues et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both methods [19], [20] have compared the proposed networks' performance with pre-trained networks such as VGG, R-CNN, GoogLeNet, and OxfordNet, demonstrating the proposed methods' superiority. In [21], an unsupervised learning method has been used with convolution layers to extract the largest area as the hand region.…”
Section: Related Workmentioning
confidence: 95%
“…BAA studies based on the deep learning algorithm are explained in the following. In [19], a compression module with 15 convolution layers and 4 pooling layers for big data compression and combined SE (squeeze-and-excitation) and ResNet with over 16 feature extraction and classification layers has presented. [20] has introduced a 15-layer convolutional network called BoNet for bone age assessment.…”
Section: Related Workmentioning
confidence: 99%
“…Larson et al (14) trained models using CNNs that were compared by radiologists, exhibiting a mean difference of 0 years between the neural network models and the BAA of radiologists, with a mean effective value and mean absolute difference (MAD) of 0.63 and 0.50, respectively. He et al (15) proposed a novel, end-to-end BAA approach that was based on lossless image compression and compressionstimulated deep residual networks. However, these methods omitted the inclusion of specific bone parts as ROIs.…”
Section: Related Workmentioning
confidence: 99%